DAMPAK PENGGUNAAN GAME ONLINE TERHADAP PEMBELAJARAN BAHASA INGGRIS (DITINJAU DARI PERSEPSI MAHASISWA) - WIJIARTI, DELLA NUR (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is entitled â€œDampak Penggunaan Game Online Terhadap Pembelajaran Bahasa Inggris (Ditinjau dari Persepsi Mahasiswa)â€. The objectives of this research are to identify and analyze the impacts and learning strategy by using online gaming in learning English based on (Cohen and Chamotâ€™s in Hinkel, 2011) theory. The learning strategies based on the function are metacognition, cognition, affection, social and based on the application are listening, speaking, writing, and reading skills. The writer uses qualitative methods in order to find out studentsâ€™ perception about the impacts and learning strategies of using online gaming in learning English. The social situation in this research is the students in English Department at the Faculty of Humanities. The writer took 11 students who use online gaming as the data of this research. The instruments of this research are interview and semi-structured question. The results of this research showed that there are some negative and positive impacts of using online gaming in learning English according to studentsâ€™ perception. Besides, there are also the learning strategies that the students uses for increasing their ability in learning English skills they are metacognition, cognition, affection, and social. This is research supports Cohen and Chamot theory about the learning strategies of using online gaming in learning English. Â Keyword: Impact, Learning Strategy, Perception, Online Gaming, Learning English